Hukum, Masyarakat Dan Kearifan Lokal Sebagai Modal Sosial Di Aceh: Catatan Awal - T. Nazaruddin; Sulaiman; Hasan Basri (SIASAT, 2019)
In the context of Aceh, its society and social-ecnonomic development, based on a number of literatures, the meaning of local wisdom can be drawn from the values, norms, laws and knowledge formed by religious teachings, beliefs, traditional values and experiences inherited from ancestors ultimately forming a local knowledge system that is used to solve everyday problems by the community. Aceh, as a region, in addition to following national law practices and provisions, also has customary institutions and traditional / cultural values with its own management that involves community leaders who know a great deal about local wisdom in the region. This is where the roles of traditional leaders, religious leaders and socio-cultural figures are considered important in harmonizing local wisdom with spatial regulation and environmentally sustainable development